Strategi Pengembangan Usaha Pembuatan Tempe Berbasis Agribisnis UD. Murni Jaya Kabupaten Pinrang (Studi Kasus UD. Murni Jaya Kab. Pinrang) - aulia muliadi; Nurhaedah Nurhaeda; Arman Arman (Jurnal Agribis, 2024)
This research aims to determine the strategy for developing an agribusiness-based tempe making business in Pinrang Regency. It will be held from December to January 2022 in Benteng Sawitto Village, Paleteang District, Pinrang Regency. This research is a case study research with the research subject namely UD's tempe making business. Murni Jaya district. Pinrang. The research method used is descriptive qualitative using strength, weakness, opportunity and thread (SWOT) analysis. The research results show that the tempe making business is in an aggressive position so that it can choose a strategy by maximizing strengths and taking advantage of opportunities. In simple terms, cell quadrant I shows that the position of tempe making has grown well but does not rule out the possibility of further development. The recommended strategy for developing a tempe making business is to improve product quality so that it can reach a wide market outside the region, improve the production process with sufficient labor so that it can continue to meet the increasing demand for tempeh, increase extensive marketing outside the region so that this product can be widely known. origin of the product's region so that this product becomes superior in its own region but the price of the product remains affordable.